Recombinant arginine‐degrading enzymes in metabolic anticancer therapy and bioanalytics. (3rd December 2014) - Stasyk, Oleh V.; Boretsky, Yuriy R.; Gonchar, Mykhailo V.; Sibirny, Andriy A.
Abstract Tumor cells often exhibit specific metabolic defects due to the aberrations in oncogene‐dependent regulatory and/or signaling pathways that distinguish them from normal cells. Among others, many malignant cells are deficient in biosynthesis of certain amino acids and concomitantly exhibit elevated sensitivity to deprivation of these amino acids. Although the underlying causes of such metabolic changes are still not fully understood, this feature of malignant cells is exploited in metabolic enzymotherapies based on single amino acid, e.g., arginine, deprivation. To achieve efficient arginine depletion in vivo, two recombinant enzymes, bacterial arginine deiminase and human arginase I have been evaluated and are undergoing further development. This review is aimed to summarize the current knowledge on the application of arginine‐degrading enzymes as anticancer agents and as bioanalytical tools for arginine assays. The problems that have to be solved to optimize this therapy for clinical application are discussed.